Suhu Optimal Ekstrak Ikan Toman Asal Kalimantan Tengah Sebagai Sumber Albumin - Firlianty Firlianty; Uras Tantulo (EnviroScienteae, 2020)
The aquatic resources in Central Kalimantan are very abundant, especially fisheries products. The nutritional content of the fisheries product has still not been well optimized. In this pandemic period,  fisheries resources have important role to increase human body immunity. Albumin in to man snakehead is very potential for nutrient fulfilment as albumin source and can increase immunity and health. Toman fish extract at optimum temperature can yield albumin extract needed for nutrient fulfilment at affordable price. The objective of the study is to determine optimum temperature that yield the extract of the highest albumin content. This study was an experimental employing Complete Randomized Design. Results showed that the highest albumin content was recorded at 50oc in the water bath for 25 min. with mean of 8.20g/dl and protein content of 9.24.